Body mass index and immune checkpoint inhibitor efficacy in metastatic cancer patients: A Brazilian retrospective study - Moreira, Raphael Brandao; Fernandes, Mauricio; Monteiro, Mariana Ribeiro; Luiz, Francine Maria Agostinho; Silva, Erika Simplicio; Andrade, Perla de Mello; Pinto, Mayara Batista; Lima, Letycia; Silva, Astrid; Nunez, Juliana; Freitas, Daniele; de Lima Araujo, Luiz Henrique; et al. (Frontiers in Urology, 2022)
Previous studies suggested that obesity pro-inflammatory state could improve immune checkpoint inhibitors (ICI) clinical efficacy. This is a retrospective, multicenter, and observational study that included patients treated in a private Brazilian Oncology Group. Primary outcomes were the association of body mass index (BMI) category with overall survival (OS) and progression free survival (PFS). Secondary outcomes were association between BMI and objective response rate (ORR). In the total cohort, 448 patients were classified as a normal weight (43%), overweight (36%), obese (17%) and underweight (4%). The patients were predominantly male gender (62%), with stage IV lung cancer (57%) and melanoma (19%). The obese group (BMI ≥ 30 kg/m2) had a not statistically significant longer median OS than the non-obese group (BMI < 30 kg/m2) - 21.8 months (95% CI NR - NR) versus 14.9 months (95% CI 8.3 - 21.5); HR = 0.82, (95% CI 0.57 - 1.18, P = 0.28). Obese patients treated with anti-CTLA4 did not reach the mOS, while the non-obese group had a mOS of 23.1 months (P = 0.04). PFS did not differ between subgroups. Obese patients had also lower ORR, but without reaching statistical significance. In conclusion, this study did not report an improved OS among high BMI patients treated with ICI.